Some Molecular Properties and Reaction Mechanism of Synthesized Isatin Thiosemicarbazone and Its Zinc(II) and Nickel(II) Complexes - Vurdu, Can Doğan; Akkaya, Yusuf; Çavuş, Muhammed Serdar; Kandemirli, Fatma; Saraçoğlu, Murat (Sciencedomain International, 2015)
The aim of this study is to 1H-Indole-2,3-dione 3-[N-(4-fluorophenyl)-thiosemicarbazone and its zinc(II) and nickel(II) complexes. The structures of the synthesized compounds were confirmed by spectral data and elemental analysis. They were optimized by B3LYP theory with different basis sets. The optimized structures were compared with the experimental values. TD-DFT calculationson electronic absorption spectra in gas phase and DMSO were performed to determine the electronic transitions of the compounds. The Frontier Molecular Orbital analysis were also done in
order to identify the charge transfer interaction that takes place between the molecular orbitals. Reaction mechanism of 1H-indole-2,3-dione-3-(N-4-fluorophenyl thiosemicarbazone) molecules were also studied.